AB1146 Musculo-skeletal pain and joint hypermobility in children: A complex relationship. (23rd January 2014) - Sperotto, F.; Balzarin, M.; Trainito, S.; Martini, G.; Zulian, F.
Abstract : Background: Benign Joint Hypermobility Syndrome (BJHS), is a non-inflammatory condition of generalized joint hypermobility (GJH) associated with musculo-skeletal symptoms such as arthralgia or myalgia in absence of other defined rheumatic diseases. Children referring musculo-skeletal pain (MSP) or growing pain (GP) often present GJH. Objectives: We aimed at clarifying the complexity of the relationship between MSP, GP, GJH and BJHS, which is due to possible overlap of these conditions and to confusing terminology. Our objectives were: 1. To determine the prevalence of GP, MSP, GJH and BJHS in children populations 2. to study the coexistence of these conditions 3. to determine the Beighton's score (BS) cut-off adopted to indicate GJH. Methods: Literature review and meta-analysis on PubMed database, using the terms "musculoskeletal pain", "growing pain", "joint hypermobility" and "benign joint hypermobility syndrome" as inclusion criteria restricted to the age range 0-18 years, were performed. The following sourches have been excluded: comments, letters, editorials, news, reviews, case reports, unavailable rough data, duplicated articles. The analysis was then split in two data collections focusing on: 1. relationship between MSP, GP and GJH as a possible cause 2. relationship between GJH and MSP or GP as possible effect. Results: Of 719 selected articles (years 1972-2011), 37 were considered pertinent. MSP analysis results (28 articles, 35 cohorts). GP frequency 20.6 - 37% of the general population, 8.2% for patients referred to primary care physicians (PCP), 25.6% in patients with concomitant GJH. MSP frequency 15% - 85% of general population, 6.1% for patients referred to PCP, 74% in patients with concomitant GJH. Pain involved sites: lower limbs 22 – 65.8%; upper limbs 7 - 20%; back 11.4 - 24%. GHJ analysis results (21 articles, 28 cohorts): GJH frequency ranging between 7, 4 (BS cut-off≥6) and 39, 4% (BS cut-off≥4) of patients with MSP, 63% among ballet dancers (BS cut-off≥4). MSP frequency: 74% of the GHJ population. Cut-off of BS chosen to indicate GJH: BS≥4 for 8 studies, BS≥5 for 5 studies, BS≥6 for 4 studies. Studies using BJHS definition reported a frequency of 4.6 – 9.2% in the general population. According with the data including patients with concomitant MSP/GP and GHJ, satisfying BJHS definition, the frequency of BJHS raises up to 6 – 34% of the general population. Conclusions: The systematic literature review shows an important overlap between MSP, GP, and GJH. Since BJHS has often negative impact on the physical and psychological well-being in pediatric age, its identification becomes essential to correctly address the problem. Therefor, GJH should be always investigated in children with non-inflammatory MSP. A general consensus on BS cut-off is needed in order to better classify patients for clinical research, epidemiology and outcome studies. References: Kirk JA, Ansell BM, Bywaters GL, The hypermobility syndrome: musckuloskeletal complaits associated with generalized joint hypermobility. Ann Rheum Dis 1967;26:419-425. Beighton P, Soloman L, Soskolne CL Articular mobility in an African population. Ann Rheum Dis 1973;32:413-8. Disclosure of Interest: None Declared